Accounting signifiers, political discourse, popular resistance and legal identity during Pakistan Steel Mills attempted privatization. (May 2019) - Ashraf, Muhammad Junaid; Muhammad, Faiza; Hopper, Trevor
Abstract: Using the privatization of Pakistan Steel Mills (PSM) as an empirical site and drawing on Laclau and Mouffe's (1985) discourse theory, this paper traces the discursive struggle between two discourses on the valuation and privatization of PSM. Specific signifiers were articulated and re-articulated into different chains of equivalence to create an appeal for each discourse surrounding the steel mill's valuation. The anti-privatization discourse's 'success' derived from its 'interdiscursivity' i.e. drawing on disparate signifiers from different meta-discourses; accounting, nationalism, state corruption and 'informal' signifiers such as 'family silver', 'market value' and 'throw away price'. In contrast, the pro-privatization discourse drew on a homogenous (financial) economics discourse using more formal and technical signifiers such as 'going concern' and 'sensitivity adjusted discounted cash flow value'. The anti-privatization discourse, with its diverse and informal (accounting) signifiers gained 'empirical validity', 'narrative fidelity', 'and experiential commensurability', appealed more to the masses, the media, and the judiciary. It convinced them selling PSM was a grave injustice, which must be prevented. Hence the Supreme Court reversed the privatization decision, which soured executive-judiciary relations, and led the military government to suspend the Chief Justice of Pakistan, and later the judiciary, media outlets, and the Constitution, which precipitated a successful social movement for an independent judiciary and the restoration of democracy. Events were shaped by the various interests of parties concerned and created new identities for them. The paper concludes by reflecting on how the findings contribute to, and add new issues for accounting research using discourse analysis.